PENGARUH PENAMBAHAN UREA DAN AMONIUM KARBONAT PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN KETEGUHAN REKAT TRIPLEKS JABON - Paribotro Sutigno; Adi Santoso Santoso (Jurnal Penelitian Hasil Hutan, 1990)
The problem in using plywood bonded with urea formaldehyde  (UF) is formaldehyde   emission, especially in a room with limited ventilation.  To  reduce  formaldehyde emission,   the glue  can be mixed  with  catching agent. In this paper the effect of  urea and  ammonium   carbonate  as catching  agent  on  formaldehyde emission   and  on  bonding  strength  of  UF bonded  three plies made from jabon  is discussed.The effect of catching agent  type on formaldehyde emission  is  not  significant    while  the  effect of percentage of catching  agent is highly  significant on  formaldehyde   emission. The  higher percentage of catching agent,  the lower formal dehyde  emission  of plywood.The effect of type and percentage  of  catching  agent  on plywood bonding strength  is  highly  significant. The  higher percentage  of catching agent,  the lower plywood  bonding strength.To meet  formaldehyde emission  of  0,165 µg/ml  it  is recomended to use urea  14%  on  the  weight basis of liquid  UF. The bonding strength  of this plywood conforms   with  the Japanese standard, 1973.